Preparation method of bifunctional nickel cobalt selenide / molybdenum selenide composite nanomaterial
By designing the heterojunction surface of nickel cobalt selenide/molybdenum selenide composite nanomaterials, the problems of low energy density and high hydrogen production technology are solved, efficient energy storage and catalytic performance are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202510092005.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-18
AI Technical Summary
The existing supercapacitors have low energy density, and hydrogen production technology relies on precious metal catalysts, which are costly and difficult to improve efficiency.
By designing a nickel cobalt selenide/molybdenum selenide composite nanomaterial with a heterojunction surface, the ion transport pathway is optimized, the core-shell heterostructure is formed, and the selenization treatment is carried out through hydrothermal method.
It significantly improves the energy storage and catalytic capacity of the material, reduces costs, reduces resource consumption, and achieves excellent conductivity, energy storage capacity, catalytic efficiency and stability.
Smart Images

Figure CN119650323A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano materials and electrocatalysis, and relates to a method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nano material. Background Art
[0002] Against the backdrop of the rapid growth of global fossil energy consumption, the utilization and development of renewable energy is limited by its intermittent nature and frequency instability. Therefore, there is an urgent need for energy storage and conversion devices such as supercapacitors that can be quickly charged and discharged, have an excellent service life and meet the highest safety standards. With these advantages, supercapacitors have become one of the most socially demanded energy storage technologies today. However, the relatively low energy density of supercapacitors limits their industrial production and commercial application.
[0003] In terms of future energy transformation, hydrogen is one of the most promising solutions to replace fossil energy because of its advantages such as high calorific value and zero pollution. Currently, the use of electrochemical water splitting (EWS) technology to produce high energy density hydrogen fuel is considered to be a promising hydrogen production technology. However, due to over-reliance on precious metal catalysts such as Pt, Ru and Ir, its commercial efficiency is still difficult to improve. In order to meet this challenge, it is necessary to seek low-cost, high specific surface area and highly active nanomaterials.
[0004] Studies have shown that there is an interaction between the negative charge of selenium and the abundant d-orbital electrons in transition metals, which promotes electron transfer in transition metal selenides (TMSe). In particular, nickel- and cobalt-based TMSe compounds are not only cheap raw materials, but also generally have higher theoretical capacitance and catalytic efficiency than sulfide and phosphide compounds, making them good raw materials for preparing bifunctional materials with supercapacitors and electrocatalytic hydrogen production. However, the structural disorder and volume expansion phenomena that often occur during the preparation process greatly damage their microstructure, resulting in the actual catalytic efficiency, rate performance and stability performance of TMSe being difficult to meet commercial usage requirements.
[0005] Through structural design, nickel-cobalt-based selenides can further promote the exposure of additional active areas, more effectively promoting their energy storage and catalytic capabilities. The construction of heterostructures is an excellent solution in various structural designs. This process can change the charge distribution between materials, generate internal electric fields, and significantly improve the electrochemical performance of electrodes. Summary of the invention
[0006] In order to solve the above problems, the present invention discloses a method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial. The present invention optimizes the ion transport pathway by designing a reasonable nanostructure with a heterojunction surface for TMSe. Specifically, a NiMoO2 composite nanostructure is constructed on nickel foam through a hydrothermal scheme. 4A core-shell heterostructure with NiCo-LDH as the core layer and NiCo-LDH as the shell layer was formed. Subsequently, these heterostructures were selenized to finally form a nickel cobalt selenide / molybdenum selenide composite heterostructure material. The d orbital electrons of Ni, Co, and Mo and the p orbital electrons of Se can produce strong interactions, optimize the charge arrangement, and effectively accelerate electron transfer, thereby significantly improving the energy storage and catalytic capabilities of the material. This method ensures that the potential of TMSe's excellent conductivity, energy storage capacity, catalytic efficiency, and stability is realized.
[0007] In order to achieve the above objectives, the present invention adopts the following technical solutions:
[0008] A method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial comprises the following steps:
[0009] Step (1) dissolving nickel salt and ammonium molybdate in water, stirring at room temperature to obtain a mixed solution A of metal salts, immersing nickel foam in the mixed solution A, heating, cooling and drying, and obtaining NiMoO 4 Nanoarrays;
[0010] Step (2) dissolving nickel salt, cobalt salt and sodium nitrate in a mixed solution of ethanol and water, stirring at room temperature until uniform to obtain a mixed solution B, and mixing the NiMoO 4 The nanoarray was immersed in the mixed solution B and heated, and then cooled and dried to obtain NiMoO 4 @NiCo-LDH nanomaterials;
[0011] Step (3) dissolving sodium borohydride in water, stirring at room temperature until uniform, obtaining a mixed solution C, adding selenium powder to the mixed solution C and continuing to stir until clear and transparent, obtaining a mixed solution D; and then adding the NiMoO obtained in step (2) to the mixed solution D. 4 The @NiCo-LDH nanomaterial is heated, then cooled and dried to obtain a bifunctional nickel cobalt selenide / molybdenum selenide composite nanomaterial.
[0012] The nickel salt is one of nickel nitrate, nickel chloride, nickel acetate and nickel sulfate, or a mixture of two or more thereof.
[0013] The cobalt salt is one of cobalt nitrate, cobalt chloride, cobalt acetate and cobalt sulfate, or a mixture of two or more thereof.
[0014] In step (1), the nickel foam is immersed in hydrochloric acid and anhydrous ethanol solutions for ultrasonic cleaning, and then vacuum dried.
[0015] In step (1), ammonium molybdate and nickel salt, wherein the molar ratio of ammonium molybdate to nickel salt is 1:6.
[0016] In step (2), the molar ratio of the nickel salt to the cobalt salt is (1-3):1; the molar ratio of the total molar amount of the nickel salt and the cobalt salt to the molar amount of sodium nitrate is 1:5.
[0017] In step (2), the volume ratio of water to ethanol in the ethanol aqueous solution is 1:2.
[0018] In step (2), the heating temperature is 100 to 150° C. and the heating time is 4 to 8 hours.
[0019] In step (3), the molar ratio of the selenium powder to sodium borohydride is 1:2, the heating temperature is 120-180° C., and the reaction time is 2-6 hours.
[0020] Beneficial effects of the present invention:
[0021] (1) The preparation method provided by the present invention is carried out through a simple hydrothermal scheme, the operation process is simple and easy, and the conditions are mild. The raw materials used do not include precious metals, the cost is low, the environment is environmentally friendly and pollution-free, and resource consumption can be greatly reduced.
[0022] (2) The present invention constructs a self-supporting nickel cobalt selenide / molybdenum selenide composite nanomaterial on nickel foam, and its structure is in the shape of uniformly staggered nanosheets, which reduces the generation of dead volume and the use of binders. In addition, during the selenization process, the initially prepared NiMoO 4 By reacting with selenium sources, part of the molybdenum selenide is released and embedded into nickel cobalt selenide, resulting in a unique modification that makes the nickel cobalt selenide nanosheets rough and stable; the interaction between the d-orbital electrons of Ni, Co, and Mo and the p-orbital electrons of Se optimizes the charge arrangement and effectively accelerates electron transfer, allowing the material to simultaneously exhibit excellent energy storage properties and electrocatalytic hydrogen production HER capabilities, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 NiMoO prepared in Example 1 4 Scanning electron microscopy images of precursor nanomaterials.
[0024] Figure 2 NiMoO prepared in Example 1 4 @Scanning electron microscope image of NiCo-LDH nanomaterial.
[0025] Figure 3 This is a scanning electron microscope image of the nickel cobalt selenide / molybdenum selenide composite nanomaterial prepared in Example 1.
[0026] Figure 4 In the figure, (a) and (b) are the prepared nickel cobalt selenide / molybdenum selenide composite nanoparticles used as electrode materials and NiMoO 4@Performance comparison of CV and GCD of NiCo-LDH precursor and comparative examples 10-11 at the same scan rate (current density).
[0027] Figure 5 In the figure, (a) and (b) are the CV and GCD performance tests of the nickel cobalt selenide / molybdenum selenide composite nanoparticles prepared in Example 1 at different scan rates / current densities.
[0028] Figure 6 This is the rate performance diagram of the nickel cobalt selenide / molybdenum selenide composite nanoparticles prepared in Example 1.
[0029] Figure 7 In the figure, (a) and (b) are respectively the nickel cobalt selenide / molybdenum selenide composite nanoparticles prepared in Example 1 as catalyst and NiMoO 4 @LSV comparison and stability effect of NiCo-LDH precursor and comparative examples 10-11. DETAILED DESCRIPTION
[0030] The specific implementation scheme of the present invention is further described in detail below through examples in combination with the accompanying drawings, but the present invention is not limited to the described implementation scheme.
[0031] Example 1
[0032] (1) Dissolve 0.25g nickel acetate and 0.2g ammonium molybdate in 30ml deionized water and stir at room temperature for 1h to obtain a uniformly mixed metal solution. Then transfer the solution to a 50ml polytetrafluoroethylene liner, immerse the nickel foam pretreated with hydrochloric acid vertically in it, and perform a hydrothermal reaction at 180℃ for 10h. After the reaction is completed and cooled, the NiMoO 4 The nickel foam was vacuum dried to obtain Figure 1 Rod-shaped precursor array material.
[0033] (2) 0.4 mmol of cobalt acetate, 1.2 mmol of nickel acetate and 8 mmol of sodium nitrate were dissolved in 30 ml of ethanol / water mixture, wherein the volume ratio of water to ethanol was 1:2, and stirred at room temperature for 30 min. After all the raw materials were dissolved, the mixture and the NiMoO grown by (1) were added. 4 The nickel foam material was transferred to a reactor and subjected to a hydrothermal reaction at 120°C for 6 hours. After cooling, the nickel foam material was vacuum dried to obtain Figure 2 The shell layer is a nanosheet and the core layer is a nanorod-shaped NiMoO 4 @NiCo-LDH nanomaterials.
[0034] (3) Take 1 mmol of sodium borohydride and dissolve it in 20 ml of deionized water. Slowly stir for 15 min. Then take 0.5 mmol of selenium powder and add it to the above solution. Slowly stir again for 15 min. When the solution becomes clear and transparent, mix the mixed solution with the NiMoO obtained in (2). 4 @NiCo-LDH nickel foam material was placed in a reactor and subjected to a hydrothermal reaction at 180°C for 8 hours. After cooling, it was vacuum dried to obtain Figure 3 Rougher and smaller nanosheet-coated nickel cobalt selenide / molybdenum selenide composite nanomaterials.
[0035] (4) The supercapacitor electrochemical performance test or water electrolysis HER test of the nanomaterial is carried out by a three-electrode system. In the supercapacitor test, the material is directly used as the working electrode, the platinum wire electrode is used as the counter electrode, Hg / HgO is used as the reference electrode, the electrolyte is 6M KOH, and the test results are not IR compensated. In the water electrolysis HER test, the material is directly used as a catalyst, the carbon rod is used as the counter electrode, Hg / HgO is used as the reference electrode, the electrolyte is 1M KOH, and the test results are 60% IR compensated to eliminate the influence of solution resistance.
[0036] (5) The obtained nickel cobalt selenide / molybdenum selenide composite nanomaterials are tested in supercapacitors. Figure 4 As shown in the figure, its CV curve has the largest coverage area and obvious redox peak, as well as the longest charge and discharge platform coverage area, showing typical battery material characteristics. The comparison of various materials also highlights its most excellent energy storage characteristics. Figure 5 In (b), it is calculated that at 3 mA cm -2 At a current density of 1.34 W, the specific capacity of the NiCoSe / MoSe composite nanomaterials reached 13.563 F cm -2 , and the current density is 3-30mA cm -2 In the range of Figure 6 ). The electrolysis of water to produce hydrogen was tested by LSV. Figure 7 Middle (a), 10 mA cm -2 At a current density of 1.3 Å, the overpotential of the NiCoSe / MoSe composite nanomaterial reached 71.2 mV, which is the optimal value for all samples, and can be used stably for more than 100 h at this current density (e.g. Figure 7 (b)).
[0037] Example 2
[0038] The difference between the embodiment and the embodiment 1 is that the amount of cobalt acetate used in step (2) is 0.53 mmol, and the amount of nickel acetate used is 1.06 mmol. The rest is the same as the embodiment 1.
[0039] The same test method as in Example 1 was used to obtain the -2 The current density reached 7.223F cm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 69% at a current density of 1.5 %.
[0040] Example 3
[0041] The difference between the embodiment and the embodiment 1 is that the amount of cobalt acetate used in step (2) is 0.8 mmol, and the amount of nickel acetate used is 0.8 mmol. The other steps are the same as the embodiment 1.
[0042] The same test method as in Example 1 was used to obtain the -2 The current density reached 6.97F cm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 72% at a current density of 1.5 %.
[0043] Example 4
[0044] The difference between this embodiment and embodiment 1 is that in step (2), 0.4 mmol of cobalt sulfate, 1.2 mmol of nickel sulfate and 8 mmol of sodium nitrate are dissolved in 30 ml of ethanol / water mixture, and the solution is heated at 100° C. for 8 h. The rest is the same as in embodiment 1.
[0045] The same test method as in Example 1 was used to obtain the -2 The current density reaches 8.9Fcm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 68% at a current density of 1.5 %.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 1 is that in step (2), 0.4 mmol of cobalt chloride, 1.2 mmol of nickel chloride and 8 mmol of sodium nitrate are dissolved in 30 ml of ethanol / water mixture, and the solution is heated at 150° C. for 4 h. The rest is the same as in embodiment 1.
[0048] The same test method as in Example 1 was used to obtain the -2 The current density reached 9.23F cm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 65% at a current density of 1.5 %.
[0049] Example 6
[0050] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction temperature in step (3) is 150° C. The other aspects are the same as those in embodiment 1.
[0051] The same test method as in Example 1 was used to obtain the -2 The current density reached 11.05F cm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 63% at a current density of 1.5 %.
[0052] Example 7
[0053] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction temperature in step (3) is 120° C. The other aspects are the same as those in embodiment 1.
[0054] The same test method as in Example 1 was used to obtain the -2 The current density reaches 9.9Fcm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 64% at a current density of 1.5 %.
[0055] Example 8
[0056] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction time of step (3) is 2 hours. The other aspects are the same as those of embodiment 1.
[0057] The same test method as in Example 1 was used to obtain the -2 The current density reaches 8.5Fcm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 58% at a current density of 1.5 %.
[0058] Example 9
[0059] The difference between this embodiment and embodiment 1 is that the hydrothermal reaction time of step (3) is 5 hours. The other aspects are the same as those of embodiment 1.
[0060] The same test method as in Example 1 was used to obtain the -2 The current density reached 11.11F cm -2 The specific capacity at 30 mA cm -2 The rate capability is maintained at 66% at a current density of 1.5 %.
[0061] Comparative Example 10
[0062] (1) Take 0.25g nickel acetate and 0.2g ammonium molybdate and dissolve them in 30ml deionized water. Stir at room temperature for 1h to obtain a uniformly mixed metal solution. Then transfer the solution to a 50ml polytetrafluoroethylene liner, immerse the pretreated nickel foam vertically in it, and perform a hydrothermal reaction at 180℃ for 10h. After the reaction is completed and cooled, the NiMoO 4 The nickel foam is vacuum dried to obtain a precursor electrode.
[0063] (2) Take 1 mmol of sodium borohydride and dissolve it in 20 ml of deionized water. Slowly stir for 15 min. Then take 0.5 mmol of selenium powder and add it to the above solution. Slowly stir again for 15 min. When the solution becomes clear and transparent, mix it with the NiMoO obtained in (1). 4 The electrode material was placed in a reactor and subjected to a hydrothermal reaction at 180° C. for 8 h. After cooling, the material was vacuum dried to obtain a nickel selenide / molybdenum selenide composite nanomaterial.
[0064] (3) The electrochemical performance of this comparative example was evaluated using the same electrochemical test method as in Example 1. -2 At a current density of 4.9 F cm -2 (like Figure 4 (b)). The current density is 3-30 mA cm -2 In the range of , the rate performance is 39%, which is significantly lower than that of Example 1. Figure 7 In the HER test results of (a), 10 mA cm -2 At a current density of , the overpotential is 156.4 mV.
[0065] Comparative Example 11
[0066] (1) 0.4 mmol of cobalt acetate, 1.2 mmol of nickel acetate and 8 mmol of sodium nitrate were dissolved in 30 ml of ethanol / water mixture (water: ethanol = 1:2), and stirred at room temperature for 30 min. After all the raw materials were dissolved, the mixture and the pretreated nickel foam were transferred to a reactor and subjected to a hydrothermal reaction at 120°C for 6 h. After cooling, the mixture was vacuum dried to obtain a nickel foam precursor material with NiCo-LDH grown on it.
[0067] (2) Take 1 mmol of sodium borohydride, dissolve it in 20 ml of deionized water, and slowly stir it for 15 minutes. Then take 0.5 mmol of selenium powder and add it to the above solution. Slowly stir it again for 15 minutes. When the solution becomes clear and transparent, put it and the NiCo-LDH electrode material obtained in (1) into a reactor and carry out a hydrothermal reaction at 180°C for 8 hours. After cooling, vacuum dry it to obtain nickel cobalt selenide nanomaterials.
[0068] (3) The electrochemical performance of this comparative example was evaluated using the same electrochemical test method as in Example 1. -2 At a current density of 1.34 W, the specific capacity is 9.9 F cm -2 (like Figure 4 (b)). The current density is 3-30 mA cm -2 In the range of , the rate performance is 45%. Figure 7 In the HER test results of (a), 10 mA cm -2 At a current density of , the overpotential is 137.8 mV.
[0069] From the above comparison, it can be found that the nickel cobalt selenide / molybdenum selenide composite nanomaterial of the present invention has excellent area specific capacitance and good rate performance, and can also show excellent HER electrocatalytic ability and good electrochemical performance of bifunctional materials.
Claims
1. A method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial, characterized in that: The steps include: Step (1) dissolving nickel salt and ammonium molybdate in water, stirring at room temperature to obtain a mixed solution A of metal salts, immersing nickel foam in the mixed solution A, heating, cooling and drying, and obtaining a NiMoO4 nanoarray; Step (2) dissolving nickel salt, cobalt salt and sodium nitrate in a mixed solution of ethanol and water, stirring at room temperature until uniform to obtain a mixed solution B, immersing the NiMoO4 nanoarray obtained in step (1) in the mixed solution B, heating, and then cooling and drying to obtain a NiMoO4@NiCo-LDH nanomaterial; Step (3) dissolving sodium borohydride in water, stirring at room temperature until uniform to obtain a mixed solution C, adding selenium powder to the mixed solution C and continuing to stir until clear and transparent to obtain a mixed solution D; then adding the NiMoO4@NiCo-LDH nanomaterial obtained in step (2) to the mixed solution D, heating it, and then cooling and drying it to obtain a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial.
2. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: The nickel salt is one of nickel nitrate, nickel chloride, nickel acetate and nickel sulfate, or a mixture of two or more thereof.
3. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: The cobalt salt is one of cobalt nitrate, cobalt chloride, cobalt acetate and cobalt sulfate, or a mixture of two or more thereof.
4. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (1), the nickel foam is immersed in hydrochloric acid and anhydrous ethanol solutions for ultrasonic cleaning, and then vacuum dried.
5. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (1), ammonium molybdate and nickel salt, wherein the molar ratio of ammonium molybdate to nickel salt is 1:
6.
6. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (2), the molar ratio of the nickel salt to the cobalt salt is (1-3):1; the molar ratio of the total molar amount of the nickel salt and the cobalt salt to the molar amount of sodium nitrate is 1:
5.
7. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (2), the volume ratio of water to ethanol in the ethanol aqueous solution is 1:
2.
8. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (2), the heating temperature is 100 to 150° C. and the heating time is 4 to 8 hours.
9. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (3), the molar ratio of the selenium powder to sodium borohydride is 1:
2.
10. The method for preparing a dual-functional nickel cobalt selenide / molybdenum selenide composite nanomaterial according to claim 1, characterized in that: In step (3), the heating temperature is 120 to 180° C. and the reaction time is 2 to 6 hours.